2020
DOI: 10.1101/2020.04.27.063404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Site-specific effects of neurosteroids on GABAAreceptor activation and desensitization

Abstract: 1This study examines how site-specific binding to the three identified neurosteroid binding sites in the 2 α1β3 GABAA receptor (GABAAR) contributes to neurosteroid allosteric modulation. We found that the 3 potentiating neurosteroid, allopregnanolone, but not its inhibitory 3β-epimer epi-allopregnanolone, binds 4 to the canonical β3(+)-α1(-) intersubunit site that mediates receptor activation by neurosteroids. In contrast, 5 both allopregnanolone and epi-allopregnanolone bind to intrasubunit sites in the β3 su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Type A GABA (GABA A ) receptors belong to the pentameric ligand-gated ion channel (pLGIC) superfamily, which includes mammalian nicotinic acetylcholine receptors (nAChRs), serotonin type 3A receptors and glycine receptors, as well as other non-mammalian homologues 14,15 . GABA A αβ receptors share common properties regardless of specific α or β subtype 16 , comprise a notable population of extrasynaptic receptors 8,[17][18][19] , and are important model receptors for understanding drug modulation 20,21 . They bear two distinct traits common to tonic GABAergic conductance.…”
mentioning
confidence: 99%
“…Type A GABA (GABA A ) receptors belong to the pentameric ligand-gated ion channel (pLGIC) superfamily, which includes mammalian nicotinic acetylcholine receptors (nAChRs), serotonin type 3A receptors and glycine receptors, as well as other non-mammalian homologues 14,15 . GABA A αβ receptors share common properties regardless of specific α or β subtype 16 , comprise a notable population of extrasynaptic receptors 8,[17][18][19] , and are important model receptors for understanding drug modulation 20,21 . They bear two distinct traits common to tonic GABAergic conductance.…”
mentioning
confidence: 99%
“…The existence of multiple functional NS binding sites on GABA A R is discussed in the literature (Chen et al, 2019). Three NS‐binding sites in the α1β3 GABA A R are identified to contribute to NS allosteric modulation (P. S. Miller et al, 2017; Sugasawa et al, 2020). The authors demonstrated that the canonical β3(+)–α1(−) inter‐subunit site mediates receptor activation by NSs, the intrasubunit site in the β3 subunit promotes receptor desensitization and another intrasubunit site in the α1 subunit promotes effects that vary between NSs.…”
Section: Discussionmentioning
confidence: 99%
“…When the predicted and observed isotherms are compared, the observed isotherms appear to contain a higher affinity population of sites than the predicted isotherm rather than a lower affinity component, which suggests that the lower slope is not the result of a population of resting (or other low affinity) receptors. We note that the muscimol binding isotherm for α1β3 GABA A receptors transiently expressed in HEK cells is steeper than observed with the stably expressed receptors, perhaps because of differences in the cell biology of the receptors (Hill coefficient 1.2; (Sugasawa et al, 2020)). It is important to note that there were no free parameters in the predicted isotherms (Fig.…”
Section: Discussionmentioning
confidence: 68%